Assessment of the Nutrient Value and In Vitro Rumen Fermentation Characteristics of Garlic Peel, Sweet Potato Vine, and Cotton Straw - Huiru Chen; Qianqian Sun; Changxin Tian; Xiangfang Tang; Ying Ren; Wenxun Chen (Fermentation)
This experiment was conducted to determine the nutrient composition of three agricultural by-products, namely garlic peel, sweet potato vine, and cotton straw, calculate their relative feeding value, effective energy value, and other indexes, and comprehensively evaluate their nutrient value by combining with rumen in vitro fermentation technology, with the aim of providing data references for the development and utilization of non-conventional feed resources for ruminants. The results showed that: 1) the dry matter (DM), ash, ether extract (EE), and crude protein (CP) contents of cotton straw were significantly higher than the other two feeds (p < 0.05), while the acid detergent fiber (ADF) and neutral detergent fiber (NDF) contents of garlic peel were highly significantly higher than the others (p < 0.05); 2) the relative feed value (DMI, DDM, TDN, RFV, and RFQ) and effective energy value (GE, DE, ME, NEm, NEg, and NEL) indexes of cotton straw were significantly higher than garlic peel and sweet potato vine (p < 0.01); 3) after 48 h of in vitro fermentation, the dry matter degradation rate (IVDMD) of sweet potato vine was significantly higher than the other two feeds (p < 0.01), and the cumulative gas productions (mL) and estimated gas parameters (a, b, a + b, and c) of sweet potato vine were significantly (p < 0.01) higher than those of garlic peel and cotton straw; 4) the sweet potato vine had lower pH but higher NH3-N compared to garlic peel and cotton straw (p < 0.05). The sweet potato vine had higher propionate, iso-butyrate, butyrate, iso-valerate, and total VFA than the other two roughages, which also had the lowest acetate-to-propionate ratio. Garlic peel produced the lowest acetate, while it produced the highest valerate (p < 0.05). These findings demonstrate that all three by-products have high potential as livestock feed based on their nutritive value parameters. Comparatively, sweet potato vines exhibit higher feeding value due to their relatively moderate NDF content and superior rumen fermentation performance.